Self Hardening Slurry Wall Installation By Hydromill At The Herbert Hoover Dike ? An Innovative Solution - Mario Mauro (Deep Foundations Institute)
In 2007 the US Army Corps of Engineers classified the Herbert Hoover Dike in Florida as a Dam Safety Action Classification (DSAC) 1 dam, and started the implementation of one of the largest dam rehabilitation projects in the nation. The construction of the cutoff wall is a key feature of this rehabilitation work to upgrade the dike to current dam safety criteria. The cutoff wall installation is currently being completed on Reach 1, which extends from Port Mayaca to Belle Glade, under a Multiple Task Order Contract based on performance specifications and stringent verification criteria. For the construction of the cutoff wall TREVIICOS selected the self-hardening slurry method. Since the cutoff wall is installed through a layer of highly variable limestone with Unconfined Compressive Strength (UCS) up to 14,000 psi, the excavation requires the use of the hydromill equipment. This is the first successful application of the hydromill technology with self-hardening slurry in a large scale project in the US. This paper presents the details of the method utilized, the quality control procedures, and the experience gained over seven miles of cutoff wall installed.